IMPACT OF FACULTY DESIGN-THINKING TRAINING ON TEACHING EFFECTIVENESS IN ENGINEERING COLLEGES IN CHENNAI: THE MEDIATING ROLES OF DESIGN-THINKING SELF-EFFICACY AND INSTITUTIONAL SUPPORT - Beula, R. Hepsiba; Radhakrishnan, M. (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The trend towards more innovative and industry-relevant engineering education has required the shift towards learner-focused pedagogy. Design thinking has become one of the potent models to help improve creativity, problem-solving, and learning through experiences in higher education. This paper examines the effects of faculty design-thinking training on teaching efficacy in engineering colleges in Chennai with specific attention to the mediating variables (design thinking self efficacy and institutional support). The research design used was quantitative and primary data used was the faculty members through a structured questionnaire. Structural Equation Modeling (SEM) was employed to analyze the data in order to test both direct and indirect links among the variables. The results indicate that teaching effectiveness is positively affected significantly by faculty design-thinking training. Also, the mediating power of design-thinking self-efficacy was identified, showing that faculty confidence in the implementation of the design-thinking principles is another essential factor in the improvement of the teaching practice. Significant mediating role was also indicated with the institutional support which is critical to note the need of organizational encouragement, resources and professional development opportunities in enabling the innovation teaching. These findings affirm the fact that individual and institutional factors are the partial mediators of the relationship existing between training and teaching effectiveness. The current study adds value to the current body of literature since it offers a holistic framework, which emphasizes that faculty development, psychological preparedness, and organizational support are connected to teaching efficacy in engineering education. The results have practical implications on policy makers and educational institutions to establish efficient faculty development programs and create facilitative institutional settings.